Altered functional connectivity between primary motor cortex subregions and the whole brain in patients with incomplete cervical spinal cord injury - Wang, Ling; Zheng, Weimin; Yang, Beining; Chen, Qian; Li, Xuejing; Chen, Xin; Hu, Yongsheng; Cao, Lei; Ren, Jian; Qin, Wen; Yang, Yanhui; Lu, Jie; et al. (Frontiers in Neuroscience, 2022)
To investigate the reorganizations of gray matter volume (GMV) in each subregion of primary motor cortex (M1) after incomplete cervical cord injury (ICCI) and to explore the differences in functional connectivity (FC) between the M1 subregions and the whole brain, and further to disclose the potential value of each M1 subregion in motor function rehabilitation of ICCI patients. Eighteen ICCI patients and eighteen age- and gender- matched healthy controls (HCs) were recruited in this study. The 3D high-resolution T1-weighted structural images and resting-state functional magnetic resonance imaging (rs-fMRI) of all subjects were obtained using a 3.0 Tesla MRI system. Based on the Human Brainnetome Atlas, the structural and functional changes of M1 subregions (including A4hf, A6cdl, A4ul, A4t, A4tl, A6cvl) in ICCI patients were analyzed by voxel based morphometry (VBM) and seed-based FC, respectively. Compared with HCs, no structural changes in the M1 subregions of ICCI patients was detected. However, when compared with HCs, ICCI patients exhibited decreased FC in visual related areas (lingual gyrus, fusiform gyrus) and sensorimotor related areas (primary sensorimotor cortex) when the seeds were located in bilateral A4hf, A4ul, and decreased FC in visual related areas (lingual gyrus, fusiform gyrus) and cognitive related areas (temporal pole) when the seed was located in the left A4t. Moreover, when the seeds were located in the bilateral A6cdl, decreased FC in visual related areas (lingual gyrus, fusiform gyrus, calcarine gyrus) was also observed. Our findings demonstrated that each of the M1 regions had diverse FC reorganizations, which may provide a theoretical basis for the selection of precise stimulation targets, such as transcranial magnetic stimulation (TMS) or transcranial direct current stimulation (tCDS), meanwhile, our results may reveal the possible mechanism of visual feedback and cognitive training to promote motor rehabilitation.